Insulin resistance: an atherothrombotic syndrome - Freeman, Mark S.; Mansfield, Michael W.; Barrett, Jenny H.; Grant, Peter J. (Thrombosis and Haemostasis, 2003)
The insulin resistance syndrome (IRS) is a clustering of atherothrombotic traits associated with increased vascular risk. We investigated the degree to which the phenotypic correlations between these traits are due to shared genetic and environmental factors.A multivariate genetic analysis was performed in 537 adults from 89 healthy white north European families. All traits showed significant heritability. BMI had significant genetic correlations with fasting insulin, systolic blood pressure (sBP), plasminogen activator activator inhibitor-1 (PAI-1) and fibrinogen and triglyceride. Fasting insulin had a significant genetic correlation with fibrinogen and triglyceride and Factor VII (FVII). Significant genetic correlations were shown between triglyceride and PAI-1, fibrinogen and FVII. PAI-1 and tissue plasminogen activator (t-PA) showed significant genetic correlation with sBP and with each other. Pleiotropy was demonstrated between fibrino-gen and PAI-1, t-PA and FVII. Significant environmental correlations were also demonstrated.This study demonstrates pleiotropy between coagulation and fibrinolytic factors. Shared genetic and environmental factors influencing haemostatic, metabolic and anthropometric traits underlie the atherothrombotic nature of the IRS.
Keywords: Pleiotropy; insulin resistance; haemostasis; genetics; families